Eccentricity: the case for undermining legal categories of disability and normalcy. Issue 3 (4th May 2017) - O'Connell, Karen
Abstract: Disability discrimination laws are directed at protecting people with disabilities, including people with 'disturbed' behaviour, or behaviour that is a manifestation of a disability, from unfavourable treatment. Yet, in doing so, discrimination laws contribute to the creation of a stigmatized and seemingly static legal category of disability. In response, this paper presents eccentricity as a 'border' region between disability and normalcy, one that can disturb the strict and stigmatizing boundary between these artificially separate categories of identity. Eccentricity, understood as a set of socially unusual or unconventional behaviours and traits, is a heightened version of the quirks and idiosyncrasies we all share, and reveals the interconnection of disability and normalcy. This paper asks whether current legal and biomedical definitions of disability, especially under disability discrimination law, have unnecessarily eradicated this rich and destabilizing category of identity and behaviour. Is law complicit in the narrowing of what it means to be 'normal', the expansion of what it means to be 'disabled' and the destruction of what would otherwise connect those two imagined states of being? This paper examines the way that law deals with eccentricity and argues that it is a concept that can potentially enrich our approach to discrimination law.